Childhood polybrominated diphenyl ether (PBDE) serum concentration and reading ability at ages 5 and 8 years: the HOME Study - Liang, Hong (Environ Int, 2018)
BACKGROUND: Polybrominated diphenyl ethers (PBDEs) exist extensively in the environment and human beings. PBDE concentrations are higher in children than adults. A previous study found that prenatal PBDE exposure was associated with decreased reading skills in children; however, evidence is limited on the potential impact of childhood exposure to PBDEs. The study examined the association between childhood PBDE exposures and reading ability in children at ages 5 and 8 years. METHODS: The study included 230 children from an ongoing prospective pregnancy and birth cohort study, the Health Outcomes and Measures of Environment (HOME) Study, conducted in Cincinnati, Ohio. Children’s serum concentrations of eleven PBDE congeners were measured at 1, 2, 3, 5, and 8 years. The Woodcock-Johnson Tests of Achievement - III and the Wide Range Achievement Test - 4 were administered to assess children’s reading skills at ages 5 and 8 years, respectively. We used multiple informant models to examine the associations between repeated measures of PBDEs and reading scores at ages 5 and 8 years. We also estimated the βs and 95% CIs of the association of PBDE measure at each age by including interaction terms between PBDE concentrations and child age in the models. RESULTS: All childhood BDE-153 concentrations were inversely associated with reading scores at 5 and 8 years, but associations were not statistically significant after covariate adjustment. For example, a 10-fold increase in BDE-153 concentrations at ages 3 and 5 years was associated with a −5.0 (95% confidence interval (CI): −11.0, 1.0) and −5.5 (95% CI: −12.5, 1.4) point change in Basic Reading score at age 5 years, respectively. Similarly, the estimates for Brief Reading score at age 5 years were −4.5 (95% CI: −10.5, 1.5) and −5.2 (95% CI: −12.2, 1.7) point changes, respectively. Serum concentration of BDE-47, −99, −100, and Sum(4)PBDEs (sum of BDE-47, 99, 100, and 153) at every age were inversely associated with reading scores at ages 5 and 8 years in unadjusted analyses. While the adjusted estimates were much attenuated and became non-significant, the direction of most of the associations was not altered. CONCLUSION: Our study has shown a suggestive but non-significant trend of inverse associations between childhood PBDE serum concentrations, particularly BDE-153, and children’s reading skills. Future studies with a larger sample size are needed to examine these associations.